153k views
1 vote
F(x) = 4x + 4 g(x) = 3x +7

1) find (f+g)(x)
2) find (f-g) (x)
3) find (f/g) (x)
4) what the domain for the answer in question 3. Use set builder notation or interval notation
5) find (f o g) (x)

User Tonny Tc
by
4.7k points

1 Answer

1 vote

Answer:

Part 1)
(f+g)(x)=7x+11

Part 2)
(f-g)(x)=x-3

Part 3)
(f/g)(x)=((4x+4))/((3x+7))

Part 4) In interval notation the domain is (-∞,-7/3) ∪ (-7/3,∞)

Part 5)
(f o g) (x)=12x+32

Explanation:

we have


f(x)=4x+4


g(x)=3x+7

Part 1) Find (f+g)(x)

we know that


(f+g)(x)=f(x)+g(x)

substitute the given functions


(f+g)(x)=(4x+4)+(3x+7)

Combine like terms


(f+g)(x)=7x+11

Part 2) Find (f-g)(x)

we know that


(f-g)(x)=f(x)-g(x)

substitute the given functions


(f-g)(x)=(4x+4)-(3x+7)


(f-g)(x)=4x+4-3x-7

Combine like terms


(f-g)(x)=x-3

Part 3) Find (f/g)(x)

we know that


(f/g)(x)=(f(x))/(g(x))

substitute the given functions


(f/g)(x)=((4x+4))/((3x+7))

Part 4) What the domain for the answer in question 3

we have


(f/g)(x)=((4x+4))/((3x+7))

we know that

The denominator of the quotient cannot be equal to zero

so


3x+7=0


3x=-7


x=-(7)/(3)

The domain is all real numbers except the number x=-7/3

In interval notation the domain is (-∞,-7/3) ∪ (-7/3,∞)

Part 5) Find (f o g) (x)

we know that


(f o g) (x)=f(g(x))

substitute


f(g(x))=4(3x+7)+4


f(g(x))=12x+28+4


f(g(x))=12x+32

therefore


(f o g) (x)=12x+32

User Webpreneur
by
4.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.